Ficcionalismo moral: uma avaliação crítica da proposta de Richard Joyce - Naidon, Karen Giovana Videla da Cunha (2016)
The overall objective of this study is to undertake a critical evaluation of Joyce's proposal for a moral fictionalism. In order to meet this objective, the thesis is divided into two main parts, the first devoted to the reconstruction of Joyce's proposal and the second reserved, properly, their critical assessment. The theme of the first chapter is the theory of moral error, focusing primarily on the defense of the same taken by Joyce. The main objective that we have to address this issue is to indicate the problem to which Joyce solution proposes its moral fictionalism, which is the question of what to do with the moral discourse after the acceptance of the theory of moral error. The second chapter is devoted specifically to the reconstruction of Joyce's proposal for a moral fictionalism. The third chapter is a summary of the main criticisms of Joyce fictionalism. In the fourth chapter, finally, it is carried critical evaluation which is the objective of this thesis. The conclusion that is reached with such assessment, which is the argument of this thesis, is that the moral fictionalism proposed by Joyce does not seem to be able to meet two specific objectives for which it was proposed, namely, (1) retain a significant portion of the practical benefits of moral beliefs and (2) prevent the one who accepts the error theory can be accused of irrationality. With this, Joyce would not able to show that adherence to error theory would not have devastating consequences, not thus fulfilling the broader objective of its proposal for a moral fictionalism. Faced with this failure, the most appropriate attitude to the theoretical error that shares Joyce s concerns and objectives appears to be intended to support here, that position that the author calls "propagandism", which seems to be the most able to meet the objectives of its proposal.